The Effect of Metformin vs Placebo on Sex Hormones in Canadian Cancer Trials Group MA.32. (4th June 2020) - Pimentel, Isabel; Chen, Bingshu E; Lohmann, Ana Elisa; Ennis, Marguerite; Ligibel, Jennifer; Shepherd, Lois; Hershman, Dawn L; Whelan, Timothy; Stambolic, Vuk; Mayer, Ingrid; Hobday, Timothy; Lemieux, Julie; et al.
Abstract: Background: Metformin has been associated with lower breast cancer (BC) risk and improved outcomes in observational studies. Multiple biologic mechanisms have been proposed, including a recent report of altered sex hormones. We evaluated the effect of metformin on sex hormones in MA.32, a phase III trial of nondiabetic BC subjects who were randomly assigned to metformin or placebo. Methods: We studied the subgroup of postmenopausal hormone receptor-negative BC subjects not receiving endocrine treatment who provided fasting blood at baseline and at 6 months after being randomly assigned. Sex hormone-binding globulin, bioavailable testosterone, and estradiol levels were assayed using electrochemiluminescence immunoassay. Change from baseline to 6 months between study arms was compared using Wilcoxon sum rank tests and regression models. Results: 312 women were eligible (141 metformin vs 171 placebo); the majority of subjects in each arm had T1/2, N0, HER2-negative BC and had received (neo)adjuvant chemotherapy. Mean age was 58.1 (SD=6.9) vs 57.5 (SD=7.9) years, mean body mass index (BMI) was 27.3 (SD=5.5) vs 28.9 (SD=6.4) kg/m 2 for metformin vs placebo, respectively. Median estradiol decreased between baseline and 6 months on metformin vs placebo (−5.7 vs 0 pmol/L; P  < .001) in univariable analysis and after controlling for baseline BMI and BMI change ( P  < .001). There was no change in sex hormone-binding globulin or bioavailable testosterone. Conclusion: Metformin lowered estradiol levels, independent of BMI. This observation suggests a new metformin effect that has potential relevance to estrogen sensitive cancers.